Quelle république pour la révolution ? - Gabriel Entin (Nuevo mundo - Mundos Nuevos, 2008)
Latin American historiography of the independence revolutions commonly associates the concept of the Republic to a non monarchical form of government. Taking into consideration the languages of three principal figures of the Rio de la Plata Revolution (Mariano Moreno, Gregorio Funes and Bernardo de Monteagudo), it is suggested that at the beginning of the revolutionary period, the republic was first conceptualized as a social value rather than as a political regime in opposition to the monarchy. We firstly describe the uses of the concept ‘republic’ in the Spanish Monarchy focusing on the relationship between the city and a Catholic world organized through the King’s authority. Secondly, we analyze the conceptual changes of the republic in the revolution of Buenos Aires, throughout its articulations with the concepts of sovereignty, law and liberty. In a context where sovereignty was discussed along with the sovereign and its representation, the analysis of the languages of Rio de la Plata revolutionaries contributes to an understanding of how the republic was envisioned during the crisis of the Monarchy and the revolutions in Latin America. This approach additionally explores the complexity of the republican theory of political liberty.